High glucose concentration abrogates sevoflurane post‐conditioning cardioprotection by advancing mitochondrial fission but dynamin‐related protein 1 inhibitor restores these effects. (26th October 2016) - Yu, J.; Maimaitili, Y.; Xie, P.; Wu, J. J.; Wang, J.; Yang, Y. N.; Ma, H. P.; Zheng, H.
Abstract: Aim: Hyperglycaemia‐induced cell injury is a primary cause of cardiovascular complications in patients with diabetes. In vivo studies demonstrated that sevoflurane post‐conditioning (SpostC) was cardioprotective against ischaemia/reperfusion injury, which was blocked by hyperglycaemia. This study investigated whether high glucose concentration abrogated SpostC cardioprotection in vitro by advancing mitochondrial fission and whether mitochondrial division inhibitor‐1 (Mdivi‐1) restored SpostC cardioprotection in cultured primary neonatal rat cardiomyocytes (NCMs). Methods: Primary cultured NCMs in low and high glucose concentrations were subjected to hypoxia/reoxygenation (H/R) injury. SpostC was carried out by adding 2.4% sevoflurane to the cells at the beginning of reoxygenation for 15 min. Cell viability, lactate dehydrogenase (LDH) level, cell death, mitochondrial morphology, mitochondrial membrane potential and mitochondrial permeability transition pore (mPTP) opening level, as well as fission‐ and fusion‐related proteins, were measured after H/R injury. Mdivi‐1 treatment was performed 40 min before hypoxia to inhibit DRP1. Results: SpostC protected cultured cardiomyocytes by increasing cell viability and reducing the LDH level and cell death following H/R, but high glucose concentration eliminated the cardioprotective effect. High glucose concentration abrogated SpostC cardioprotection via mitochondrial fragmentation (evidenced by decreased mitochondrial interconnectivity and elongation) and facilitation of mPTP opening. Decreased mitochondrial membrane potential was investigated with increased DRP1, FIS1 and MFN2 and decreased MFN1 and OPA1 expressions. Mdivi‐1 (100 μ mol L −1 ) inhibited excessive mitochondrial fission and restored the cardioprotective effect of SpostC in high glucose conditions. Conclusion: SpostC‐induced cardioprotection against H/R injury was impaired under high glucose concentrations, but the inhibition of excess mitochondrial fission restored these effects.